2014
DOI: 10.3747/pdi.2012.00077
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis by Peritoneal scintigraphy of Peritoneal Dialysis–Associated Hydrothorax in an Infant

Abstract: in-adultsclinical-manifestations-and-diagnosis?source=search_ result&search=Clinical+manifestations+and+diagnosis+ of+Clostridium+difficile+infection+in+adults&selected Title=1~139; accessed 25 June 2013] 2. Seppälä K, Hjelt L, Sipponen P. Colonoscopy in the diagnosis of antibiotic-associated colitis. A prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Both ultrasound and X-ray can confirm the presence of effusion, but not the source of the fluid. Peritoneal scintigraphy is considered an excellent modality to diagnose a pleuroperitoneal leak, but the sensitivity has been reported to be only 40% to 50%, and its utility in locating the site of the pleuroperitoneal communication is limited [ 4 , 7 , 9 ]. In a case report, Kang and Kim suggested that CT peritoneography with intraperitoneal contrast could confirm and locate the pleuroperitoneal fistula [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both ultrasound and X-ray can confirm the presence of effusion, but not the source of the fluid. Peritoneal scintigraphy is considered an excellent modality to diagnose a pleuroperitoneal leak, but the sensitivity has been reported to be only 40% to 50%, and its utility in locating the site of the pleuroperitoneal communication is limited [ 4 , 7 , 9 ]. In a case report, Kang and Kim suggested that CT peritoneography with intraperitoneal contrast could confirm and locate the pleuroperitoneal fistula [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Pathogenesis of peritoneal dialysis catheter-associated hydrothorax has been reported to originate from congenital or acquired defects of the diaphragm, defective lymphatic drainage, and pleuroperitoneal communication via a fistulous tract. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Like the symptoms of local edema, symptoms of hydrothorax often manifest upon dialysate influx, or directly after indwelling [68]. Because these symptoms could be misdiagnosed as congestive heart failure or inadequate dialysis, an early and accurate diagnosis is crucial to management.…”
Section: Hydrothoraxmentioning
confidence: 99%
“…Additionally, the presence of increased glucose levels in the pleural fluid is suggestive of a pleuro-peritoneal communication, although this does not manifest in all patients and should not be relied upon as the sole means of diagnosis [59,70,72]. Instead, there is increasing use of peritoneal scintigraphy [68,69,[73][74][75][76], which allows not only for accurate diagnosis of fluid overload and transudative pleural effusion but also allows for the identification and localization of diaphragmatic defects without thoracoscopic intervention.…”
Section: Hydrothoraxmentioning
confidence: 99%
See 1 more Smart Citation